The correlation between communication and social skills among early schoolers in Malaysia - Mahyuddin, Rahil; Elias, Habibah (Universiti Putra Malaysia Press, 2010)
Innumerable studies have shown that being able to express oneself clearly and understand with equal clarity what other people are saying to you are fundamental enabling skills of life. A proficiency at interpersonal communication is strongly linked to educational achievement and positive social behaviour. Socio-economic status (SES) has also been known for a long time to be a powerful predictor of children’s development (e.g. Deutsch, 1973; Sameroff and Chandler, 1975; Scott-Jones, 1984). In this study, communication refers to oral language skills which include the development of narrative ability, as well as the use of talk and varied vocabulary usage (Dickinson and Tabors, 2001). Hence, the objective of this paper is to find out the communication and social skills of the pupils and to see whether there is a relationship between communication skills and social skills of early schoolers and their impact on school academic achievement. This study focused on Year 1 and Year 4 primary school children, and for this purpose, a descriptive correlational method was employed. It was carried out on 344 primary school pupils, of which 168 were from Year 1 and 176 were Year 4 pupils. The pupils in the sample were academically weak and they had undergone screening and diagnostic tests. The findings indicate that the social skills of Year 1 pupils were significantly and positively correlated with their communication skills (r=.31, p<.05) and language acquisition (r=.33, p<.05), whereas the social skills of Year 4 pupils were found to be significantly and positively correlated with their language acquisition (r=.59, p<.05), Mathematic acquisition (r=.41, p<.05), and their communication skills (r=.50, p<.05). There is also a positive and significant relationship between communication (r=.81, p<.05) and social skills ( r = .85, p< .05) with family background. These findings show that social skills are very important as children enter primary school. The significant correlations between social skills and language acquisition, Mathematic acquisition and communication skills show that their performance can be negatively affected if they do not acquire the social skills.